Recognised and Harmed: A Classification Approach to Facial Recognition Technologies - Bouchagiar, Georgios (Ethics International Press Limited, 2023)
Private face recognition technologies are increasingly entering the private and public sphere, with no adequate checks and balances. This comprehensive and important new reference work explores crucial regulatory challenges, stemming from the use of private face recognition technologies in Europe. After detecting technological neutrality in law, legal uncertainty in case law and the risk of over-surveillance, it recommends an ex ante and targeted classification approach with a view to minimising privacy harms. Under the proposed scheme, an expert agency can scrutinise a given technology, balance conflicting stakes, classify that technological use and, finally, give a 'go', 'no-go' or 'go-in-condition' decision, before its actual implementation in the real-world. Recommended for legal and technology researchers and scholars focusing on surveillance and privacy, as well as government, regulatory and civil rights agencies.